To determine the equation of the horizontal line that passes through the points (−4, 4), (0, 4), and (4, 4), we observe that all these points have the same y-coordinate of 4. Therefore, the equation of this horizontal line is:
\[ y = 4 \]
Now, let's consider the second line that passes through points (0, -3) and (3, 0). We can find the slope (m) of this line using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{0 - (-3)}{3 - 0} = \frac{3}{3} = 1 \]
Next, we can use the point-slope form of the equation of a line, which is:
\[ y - y_1 = m(x - x_1) \]
Using the point (0, -3):
\[ y - (-3) = 1(x - 0) \] \[ y + 3 = x \] \[ y = x - 3 \]
To express this equation in standard form \(Ax + By = C\), we rearrange it:
\[ x - y = 3 \]
So, the standard form of the equation for the line passing through (0, -3) and (3, 0) is:
\[ x - y = 3 \]
To summarize, here are the equations of the lines:
- Horizontal line: \(y = 4\)
- Line through (0, -3) and (3, 0): \(x - y = 3\)